Cognitive-behavioural treatment of functional neurological symptoms (conversion disorder) in children and adolescents: A case series. (March 2019) - McFarlane, Fiona A.; Allcott-Watson, Hannah; Hadji-Michael, Maria; McAllister, Eve; Stark, Daniel; Reilly, Colin; Bennett, Sophie D.; McWillliams, Andrew; Heyman, Isobel
Abstract: Aim: To describe a cognitive-behavioural treatment and clinical outcomes in a series of children with functional neurological symptoms (FNS). Method: Thirty-six children with FNS were assessed and of these twenty-two (13 male, 9 female) with a mean age 14.5 years (SD = 2.6, range 6–17 years) completed treatment with cognitive behaviour therapy embedded in routine child and adolescent clinical/systemic practice. Treatment outcomes were measured at baseline and post-intervention on the Child Global Assessment Scale (CGAS), Strengths and Difficulties Questionnaire (SDQ), Goal Based Outcomes (GBO) and Revised Child Anxiety and Depression Scale (RCADS). Results: Scores on the CGAS improved significantly post-intervention (p < 0.001) with 82% of participants showing reliable change. Individualised goals (GBO) also showed clinically meaningful gains. Standard measures of emotional and behavioural symptoms (SDQ and RCADS) did not correlate well with clinical diagnoses, were usually subthreshold at baseline, and did not show significant improvement post-intervention. Interpretation: The outcome of this pilot study suggests that CBT can be effective in the rehabilitation of young patients with FNS. Detection of common comorbid psychiatric disorders was not assisted by use of standardised measures, although most participants were clinically anxious or depressed. More research is needed to understand why children with FNS and their parents may not endorse mental health symptoms on questionnaires, and to further evaluate interventions within randomised controlled trials. Highlights: Cognitive-behavioural treatment for childhood functional neurological symptoms is described in a case series. The intervention results in improved functioning. The majority of these children had clinical diagnoses of anxiety and/or depression. Standard questionnaires do not detect anxiety/depression in this population.